Application of Finger Print Attendance in Improving Employee Discipline at the Medan District Attorney's Office - Silvia Handayani Siregar; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
In order to improve employee discipline in government agencies towards professionalism and support the creation of good governance in an integrated manner with fingerprint attendance, which is a machine with the help of software to fill in the attendance data of communities, groups and agencies that use it. The purpose of this study was to see to what extent the application of finger print attendance in improving employee discipline at the Medan public prosecutor's office. The research method used is a qualitative method. The results show that the application of finger print attendance at the Medan District Attorney's Office until now can have an effect on increasing discipline on the employee attendance schedule.